Pengaruh pemberian sampah organik terhadap pertumbuhan dan kandungan astaxanthin pada pupa black soldier fly (Hermetia illucens (Linnaeus)) - Sidauruk, Arkhey; Prasetyaningsih, Aniek; Madyaningrana, Kukuh (Perhimpunan Entomologi Indonesia, 2024)
Black soldier flies (Hermetia illucens (Linnaeus)) or BSF are insects that process organic waste, with larvae rich in nutrients and potential as an alternative protein source for food and feed. Astaxanthin, an antioxidant found in plants, algae, and crustaceans, is also assumed to be present in insects like BSF. This study examined the impact of feeding different organic wastes on BSF larval growth and astaxanthin content in its pupae. The experimental design involved four treatments: fruit and vegetable scraps (BS), tofu pulp (AT), rice leftovers (N), and a mix of fruit and vegetable scraps, tofu pulp and rice left-over (C), with animal feed T51 as control. Each treatment was repeated three times. Growth parameters of BSF such as weight, length, and larval characteristics, along with the chemical content of pupae, including astaxanthin, were measured. Pupae were extracted using a triphasic maceration method with n-heptane, ethyl acetate, acetonitrile, butanol-l, and distilled water. Compound identification was done using terpenoid qualitative tests, thin layer chromatography (TLC), and liquid chromatography-mass spectrometry (LC-MS). The findings revealed that fruit and vegetable scraps (BS) significantly increased larval body size, with a weight of 0.09 ± 0.04 grams/larvae and a length of 1.49 ± 0.31 cm/larvae. LC-MS analysis detected lutein derivatives, anisodamine, resveratrol derivatives, dehydroarginine, and astaxanthin derivatives with a molecular mass of 597.23 m/z in BSF larvae fed on fruit and vegetable scraps.